A case of tribal defilement in a Kenyan rural village: A narratological and socio-rhetorical function of the motifs of "hearing and understanding" and "contrast" in Matthew 15:10–11 vis-à-vis Leviticus 11:1–4 - M’bwangi, Ferdinand M. (HTS teologiese studies, 2011)
This article employed a case study to explore the theme of defilement as experienced in a Kenyan village. To provide a basis for the theological reflection on this case study, the article investigated two motifs in Matthew 15:10–11. ‘Hearing and understanding’ and ‘contrast’ [[Refer to PDF], ‘not…but’] was examined in respect of Leviticus 11:1–8 to determine the extent to which Matthew 15:10–11 depicts Jesus as ‘relativising’ the Mosaic law (Lv 11:1–8). This approach provided a basis to argue that defilement in Matthew 15:10–11 is not only a matter of external or ritual perspective, but of moral disposition. A methodology that combines both socio-rhetorical (Socio-rhetorical criticism is a methodology that derives value and meaning as an outcome of an active reading process that occurs within specific cultural contexts. In this case, the examiner produced the meaning of given texts by participating in a complex of socially constructed practices’ [Growler n.d., http://userwww.Service.emory. edu/~dgowler/chapter.htm]) and narratological (Narratological criticism is the study of narratives that involves a kind of ‘structure and practice that illuminates temporality and human beings as temporal beings’. Using classifications such as plot, narrator and narratee, narratology becomes a useful instrument for the description, classification and interpretation of literary narratives [see http://www.hum.aau.dk/~yding/storytelling/narratology%20rerevisited. pdf]) approaches were engaged as the most appropriate to address the concerns of this article. These two methodologies greatly helped this article to explain the meaning and significance of defilement in Leviticus 11 with respect to the theological understanding of the Leviticus code of purity. This code presents a temporal view of defilement intended to reflect on the holiness and sovereignty of Yahweh, over and against idols of the surrounding nations. In addition, this kind of methodology facilitated an interpretation of the motif of ‘contrast’ [[Refer to PDF], ‘not but’] in Matthew 15:11 as the evangelist’s intentional attempt to depict Jesus intensifying the Leviticus code of ritual purity within an ethical frame work. The village case study was surveyed, exegesis done on Matthew 15:10–11 with respect to Leviticus 11:1–8, the perception of defilement for 1st century Jews assessed and a brief comparative study of the findings from Matthew 15:10–11 engaged with a Kenyan village-case study for ethical reflections. This case study pointed out that cultural difference prompted a major tribe (Wataita) to consider a minor tribe (Wasanye) to be defiled, albeit the minor tribe did not describe the major tribe in the same derogatory term.